Romances rebeldes - a tradição de rebeldia na literatura norte-americana: de Moby Dick a On the Road - Santos, Renato Alessandro dos [UNESP] (2015)
It is possible to identify in American Literature the existence of a tradition of resistance and rebellion that begins in the 19th century with Henry David Thoreau and extends throughout the 20th century. That tradition includes works in prose and verse that express artistic, cultural and social discontent and that criticize modern civilization, often employing the theme of travelling and portraying incidents in the lives of characters who are always on the move. Using and questioning the concept of tradition as expressed by T.S. Eliot, Octavio Paz and Robert Spiller, in the light of what we call a tradition of rebellion, this thesis analyses, six novels of that tradition: Herman Melville's Moby Dick, Mark Twain's The Adventures of Tom Sawyer and The Adventures of Huckleberry Finn, Jack London's Call of the Wild, Ernest Hemingway's The Sun Also Rises and Jack Kerouac's On the Road